2009
DOI: 10.1021/jf9016338
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and Electrophoretic Characterization of Select Edible Nut Seed Proteins

Abstract: The solubility of almond, Brazil nut, cashew nut, hazelnut, macadamia, pecan, pine nut, pistachio, walnut, and peanut proteins in several aqueous solvents was qualitatively and quantitatively assessed. In addition, the effects of extraction time and ionic strength on protein solubility were also investigated. Electrophoresis and protein determination (Lowry, Bradford, and micro-Kjeldahl) methods were used for qualitative and quantitative assessment of proteins, respectively. Depending on the seed, buffer type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 44 publications
(57 reference statements)
10
24
0
1
Order By: Relevance
“…These authors solubilized nut proteins from defatted nut flour and then investigated their SDS-PAGE profiles without applying isoelectric precipitation of proteins. There were some differences in the band intensities and profiles obtained by these authors and those obtained by the current study for hazelnut proteins, but concentration of most intensive protein bands determined by Sathe et al (2009) between 20 and 30 kDa (close to 20 kDa) compared well with the results of current study.…”
Section: Color Of Edible Filmssupporting
confidence: 77%
See 3 more Smart Citations
“…These authors solubilized nut proteins from defatted nut flour and then investigated their SDS-PAGE profiles without applying isoelectric precipitation of proteins. There were some differences in the band intensities and profiles obtained by these authors and those obtained by the current study for hazelnut proteins, but concentration of most intensive protein bands determined by Sathe et al (2009) between 20 and 30 kDa (close to 20 kDa) compared well with the results of current study.…”
Section: Color Of Edible Filmssupporting
confidence: 77%
“…Moreover, these authors did not determine any minor hazelnut protein fractions between pI 7.0 and 8.5. However, it is hard to understand the reasons of differences between results of Sathe et al (2009) and the current work which uses different material (defatted and acetone treated meal) and different methods for extraction, purification and isoelectric focusing of protein. On the other hand, the MW pattern of HPI-AW proteins obtained by a Different letters in each column show significant differences at P < 0.05. the 2D electrophoresis was quite similar with that obtained with the classical SDS-PAGE.…”
Section: -D Electrophoresis Patterns Of Isolated Proteinsmentioning
confidence: 96%
See 2 more Smart Citations
“…The samples extracted 1:10 (w/v) should have contained a theoretical concentration of 25 mg/mL if all of the protein in the kernel was solubilized and subsequently extracted. Sathe et al also found that extractable protein for peanut as determined by the Bradford method was somewhat lower that the theoretically expected value based on the nitrogen content of peanut kernels (Sathe et al, 2009). This can be due to incomplete extraction (Leco analysis measures the nitrogen content in the solid material of peanut, independent on extractability or solubility of different proteins), or because the two methods are calibrated by different means.…”
Section: Protein Content Of Peanut Kernels and Aqueous Extractsmentioning
confidence: 93%